A fauna de microgastrinae (Hymenoptera:Braconidae) em fragmentos de Mata Atlântica do Estado de São Paulo - Bortoni, Marco Aurélio (Universidade Federal de São Carlos, 2013)
The Braconidae has been extensively used in biological control programs in tropical and subtropical agroecosystems. Species of the subfamily Microgastrinae are subject to agrarian, ecological and biological studies because of its taxa and diversity. They constitute the most important group of parasitoids of Lepidoptera. Taxonomic works have been mainly directed to studying the fauna of temperate regions, the tropics fauna is poorly known. This study aimed to contribute to the knowledge of the Microgastrinae fauna from localities of Atlantic Forest in the State of São Paulo, supporting further taxonomic, systematic and conservation studies. In each locality five Malaise traps were installed; during 24 months, and the abundance and wealth for each genus found by calculating the values of the Shannon diversity index and Pielou Equitability index. The Bray Curtis similarity coefficient was used for comparisons of the fauna from the different localities and a cluster analysis was proposed. The total of 4,402 specimens of Microgastrinae were sampled, distributed in 23 genera. The Parque Estadual de Intervales was the site with the largest number of specimens collected, 71% of the total obtained, with 22 genera identified. The most abundant genera were Apanteles (46.18%), Glyptapanteles (18%) and Diolcogaster (10.69%). As the result of this research, a checklist of Braconidae species for the State of Sao Paulo was proposed and the description of the male of Prasmodon eminens Nixon, 1965 (Braconidae, Microgastrinae) was done.
Keywords: Diversidade biológica; Parasitóides; Taxonomia; CIENCIAS BIOLOGICAS::ECOLOGIA